Using flock simulations for modern goat market systems in Central Mozambique - Homann-Kee Tui, Sabine; Sisito, Givious; Quembo, Carlos; Sixpence, Claudio (2019)
In marginal and high-risk farming areas like Marara District in Central Mozambique, goats are a quick investment pathway for smallholder farmers and can enhance the benefits from agriculture. The current goat value chain involving sales at the feira (informal goat sales venues), with unscrupulous intermediaries, does not enhance the development of smallholder farmers. Those with small flocks cannot participate in goat markets while those with large flocks are not motivated to use their flocks more productively. As a result, the entire community operates below potential. Goat farmers and buyers are far apart, both geographically and in terms of understanding and co-operation. Enhancing communities’ capacity to organize and manage decentralized goat markets can benefit smallholder farmers immensely. Volumes and quality of goat sales can be increased by addressing the needs and interests of owners of larger and smaller flocks alike within the same community. A community-based goat market system builds social responsibility and helps communities to manage risk. The private sector has also expressed an interest to invest for enhancing communities’ technical capacity...